2018
DOI: 10.1097/grf.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Care of Lesbian and Bisexual Women for the Obstetrician Gynecologist

Abstract: Sexual minority women are more likely to delay care, less likely to have a usual place of care, and more likely to exhibit higher risk behaviors such as smoking, obesity, heavy drinking resulting in a disproportionate number of chronic conditions. It is imperative for obstetrician-gynecologists to be at the forefront of providing comprehensive health care to all women, no matter their sexual orientation. This article seeks to discuss health care disparities as well as health behaviors and outcomes in this popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
0
9
0
5
Order By: Relevance
“…Because the majority of LGBTQ+ people with HIV/AIDS in the early days of the disease were men, the specific health needs of lesbian and bisexual women were often overlooked. However, there are a number of specific health disparities affecting these women, both in regard to increased risk of certain diseases and in decreased usage of preventative care such as mammography and Pap smears [37]. Considering that these disparities exist, the lack of specific resources for cisgender LGBTQ+ women in the research guides was surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Because the majority of LGBTQ+ people with HIV/AIDS in the early days of the disease were men, the specific health needs of lesbian and bisexual women were often overlooked. However, there are a number of specific health disparities affecting these women, both in regard to increased risk of certain diseases and in decreased usage of preventative care such as mammography and Pap smears [37]. Considering that these disparities exist, the lack of specific resources for cisgender LGBTQ+ women in the research guides was surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Há formas de se remover tais barreiras partindo dos profissionais, estabelecendo um ambiente acolhedor, perguntando sobre orientação sexual e identidade de gênero, formulando perguntas para evitar a suposição de heterossexualidade e fornecendo cuidados transculturais. (RULLO e FAUBION, 2017) O médico tem papel crucial no processo de acolhimento da população LGBT, sendo de suma importância aconselhar os pacientes sobre saúde sexual de maneira inclusiva (MCCUNE et al, 2020). O padrão de formação médica é baseado numa suposta heteronormatividade, reforçando as atitudes dos profissionais de que todas as mulheres são heterossexuais e afastando o paciente de um atendimento holístico.…”
Section: Medidas Inclusivasunclassified
“…A fim de contornar essa situação, deve-se fazer uma anamnese completa, com uma história que inclua o sexo atribuído no nascimento e o sexo da parceria da paciente, bem como o tipo (oral, vaginal e/ou anal) de relação sexual em ela se envolve (MCCUNE et al, 2020).…”
Section: Medidas Inclusivasunclassified
“…32 Homo and bisexual women have fewer chances of being offered to undergo a cytopathological cervical examination and are exposed to acts of violence during the procedure, such as the use of a speculum of an inadequate size and without the necessary lubrication. 33 To assess the knowledge, attitudes, and cultural competency of undergraduate nursing students in serving the LGBTI+ population, researchers performed an educational intervention and applied an Attitude Scale Concerning Lesbian and Gay Men before and after the intervention. The results evidenced a statistically significant increase in the students' positive attitudes and knowledge level and showed that the inclusion of the contents about health care for the LGBTI+ population in the curricula contributes to the promotion of the students' cultural competency and sensibility to the subject.…”
Section: Nursing Lgbti+ Population and Primary Carementioning
confidence: 99%